Pengaturan Bentuk Usaha Penanaman Modal Asing di Indonesia - Hamam Febrian Cahaya; I Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna (Fakultas Hukum, Universitas Warmadewa, 2021)
The regulation on the establishment of a foreign investment business entity in the field of export services trade has been promulgated through Law Number 25 of 2007 concerning Investment, as contained in Article 5 paragraph 2 it is determined that the company defined according to the article which applies to everything or the largest discount in Indonesia as a single entity, the company itself is required to have been formed into a legal entity according to Indonesian positive law and domiciled in Indonesia. This study aims to determine the arrangements for the establishment of foreign investment business entities in the export trade service sector, and to determine the policies and legal instruments implemented by the Regional Investment Coordinating Board in improving the foreign investment climate in the export trade sector. The research method used is the normative legal research method. Sources of legal materials used are divided into primary, secondary and tertiary legal materials. The results showed that the regulation on the establishment of a PMA business entity in the field of export services is regulated in the PM Law in Chapter IV Legal Forms, Position and Business Area, as contained in Article 5 paragraph 2, it is stated that the company referred to in foreign investment is obliged to be in the form of a PT on the basis of positive law in Indonesia and is in the territory of the Republic of Indonesia, unless otherwise stipulated by the Law. Legal entities in Indonesia are limited liability companies that have their own fundamentals as stated in Article 1 of the PT Law is a legal entity that stands on an agreement that carries out active business on the basis of assets that have been divided into capital injected by investors and have met all the requirements stipulated in this law and in its implementing regulations.